Electrical characterizations of MgO-ZrO2 high temperature sol-gel insulations coatings on different types of epoxies - (:unkn) unknown (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2008)
The sol-gel MgO-ZrO2 electrical insulations were coated on Stainless-Steel-304 (SS) tapes by reel-to-reel process for investigation of electrical properties under various pressure at room temperature (298 K) and liquid nitrogen temperature (77 K) for HTS/LTS high field insert coil. Solutions consist of Mg and Zr based precursors, solvent and chelating agent. The electrical insulation was made on long-length SS substrate. Insulation thickness for 4, 8, and 9 dippings were determined 7, 12, and 13 mu m, respectively. Three different types of stycast, 2850 FT/24 LV Black and Blue, and White Buecher Epoxide Resin were studied. Stycast thicknesses were varied from 33-20 mu m, when the pressure was applied from 0 to 0.54 GPa. The thicknesses of high temperature insulation coatings and epoxsies were measured by using Environmental Scanning Electron Microscope (ESEM). Resistance, capacitance and High Voltage Breakdown (HVbd) Of the samples were measured by using standard machines Model 6517A Electrometer/High Resistance Meter, 161 analog digital capacitance meter and Model 200-02R High Voltage Power Supply, respectively. The results were presented graphically.
Keywords: dielectric constant; epoxy; high voltage breakdown; MgO-ZrO2 insulation; sol-gel; MAGNET TECHNOLOGY; CERAMIC INSULATION; VOLTAGE BREAKDOWN; PHASES; TAPES